Cytotoxic and apoptotic effects of curcumin and thymoquinone on HSC-2 cell line - Saleem, Khadeeja (2021)
Cancer is one of the most prevalent causes of mortality and morbidity amongst humans. Oral cancer is the 11th most common cancer. Oral squamous cell carcinoma accounts for 90% of all oral malignancies. The current commonly-practiced treatment options for oral cancer are surgery, radiation and chemotherapy. These are extremely expensive and aggressive treatment options that fail to completely eradicate the tumor and have multiple debilitating outcomes. There is a thus a strong need for better and safer treatment options. One such option is the use of naturally-occurring compounds that have cytotoxic and anti-cancer properties. Curcumin and thymoquinone are two such compounds. They are both plant-derived chemicals (phytochemicals) which are the active constituents of Curcuma longa and Nigella sativa respectively. Both these chemicals have been used for centuries to help treat various diseases. Their roles as cytotoxic and anticancer agents have been extensively studied. In this study, we test their cytotoxic and apoptotic effect on HSC-2 cell line, a type of oral squamous cell carcinoma. The cytotoxic properties were evaluated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay at various concentrations (7.8μM-250μM) for 24, 48 and 72h. The results from MTT assay showed significant decrease in cell viability of the HSC-2 cells at 24h and so, 50% inhibitory concentration (IC50) was calculated at this time and was found out to be 54.47μM and 32.70μM for curcumin and thymoquinone respectively. Their apoptosis inducing property was confirmed via flow cytometry using the Annexin V apoptosis detection kit. The results showed a significant percentage of early apoptotic cells for curcumin (mean= 9%) and thymoquinone (mean= 8%) at 24h at the concentration of 62.5μM. The results obtained from these experiments support the established cytotoxic and anti-proliferative properties of curcumin and thymoquinone and support results from similar studies.